FEMINISME PADA NOVEL SURGA YANG TAK DIRINDUKAN KARYA ASMA NADIA - Diah Retno Wulandari (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2021)
The purpose of this study was to describe (1) the views gender of women in the novel Heaven is Not Missed by Nadia, Asma on several aspects of their live; (2) the gender injustice suffered by women in the Novel Heaven is Not Missed by Nadia, Asma: (3 ) women ‘s resistance in the Novel Heaven is Not Missed by Nadia, Asmaagainst injustice they live. The research uses a sociological approach. Theoretical basis used is (1) the concept of feminism studies, (2) the concept of women ‘s perspectives, (3) the concept of women and injustice, (4) the concept of women ‘s resistance in the literature. Source of data used (1) Novel Heaven is Not Missed by Nadia. The technique used in collect the data is reading and note technic. Data analysis was performed based on techniques in conducting studies of feminism, namely (1) identifying one or more female characters in a literature, (2) examine another character, especially male figures relating to the female characters in the literature, (3) observing the am rude of the writer in the literary work. Based on the analysis, obtained : (1) the view gender that there are women in the Novel Heaven is Not missed by Nadia, Asma (2) form of gender injustice experienced by women in the Novel Heaven is not missed by Nadia, Asma, (3) resistance of women in the Novel Heaven is Not Missed by Nadia, Asma.